Obstetric critical care services in South Africa - Gladness Nethathe; Edward Buga; Lufuno Mathivha (South African Medical Association, 2015)
More than half of all global maternal deaths occur in Africa. A large percentage of these deaths are preventable, and lack of access to adequate critical care facilities is a contributing factor. There are limited published data on the clinical and management challenges presented by the critically ill obstetric patient admitted to the intensive care unit in our setting, and more data are required in order to better define the critical care needs of this group of patients.